Efficient and Greener Synthesis of Functionalized Isoniazid Azomethines from Aromatic Aldehydes and Isatins Using Citric Acid in Aqueous Ethanol. (2nd January 2023) - Wagh, Yogesh B.; Dalal, Kiran S.; Padvi, Swapnil A.; Terdale, Santosh S.; Dalal, Dipak S.; Mahulikar, Pramod P.
Abstract: Citric acid was discovered as an efficient catalyst for the rapid synthesis of pharmacologically important isoniazid azomethines by condensation of aromatic aldehydes and isatins with isoniazid in aqueous ethanol under reflux condition. The advantages of the described method include the use of readily available starting materials, biodegradable greener catalyst, and mild reaction conditions. The products were obtained in high yield within short reaction time and no need for column chromatography purification. Graphical Abstract: UF0001